Shale gas : the facts about chemical additives - Craddock, Henry (Knovel, 2012)
"North America is undergoing a boom associated with the production of natural gas from dense shale rock formations via the combination of two established technologies - hydraulic fracturing and horizontal drilling. This article focuses on the technique of hydraulic fracturing and in particular the common chemical additives used to support this technique."--Knovel.